2018
DOI: 10.1007/s00424-018-2200-6
|View full text |Cite
|
Sign up to set email alerts
|

Renal expression and urinary excretion of Na+/dicarboxylate cotransporter 1 (NaDC1) in obstructive nephropathy: a candidate biomarker for this pathology

Abstract: Obstructive nephropathy is characterized by alterations in renal function that depends on the degree and type of obstruction. To increase the knowledge about the physiopathological mechanisms involved in the renal damage associated with bilateral ureteral obstruction (BUO), we studied the renal expression and function (as urinary citrate excretion) of sodium-dependent dicarboxylate cotransporter (NaDC1) in rats. In addition, we evaluated the urinary excretion of NaDC1 as a candidate biomarker for this patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Each value represents mean ± standard error from experiments carried out in triplicate on four different tissue‐derived samples or urine‐derived samples for each experimental group. The protein abundances of Oat5 and NGAL in the urine samples were expressed as optical density (O.D., arbitrary units) related to urinary creatinine concentration ([O.D./10 μL]/Cr U ) in order to correct for variations in urine production as previously reported …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each value represents mean ± standard error from experiments carried out in triplicate on four different tissue‐derived samples or urine‐derived samples for each experimental group. The protein abundances of Oat5 and NGAL in the urine samples were expressed as optical density (O.D., arbitrary units) related to urinary creatinine concentration ([O.D./10 μL]/Cr U ) in order to correct for variations in urine production as previously reported …”
Section: Methodsmentioning
confidence: 99%
“…For densitometry of immunoblots, samples from treated rats were in order to correct for variations in urine production as previously reported. 10,11,14,46,49…”
Section: Electrophoresis and Immunoblottingmentioning
confidence: 99%
“…Several experimental models have been used as insight into the pathophysiology of postrenal injury. The surgical procedure of complete obstruction of both ureters has been used in our laboratory and also by other authors 19,21,22 . Campagno et al 21 have recently demonstrated modifications in renal haemodynamic and in some tubular function parameters, as well as in the renal architecture after 5 and 24 hours of bilateral ureteral obstruction.…”
Section: Discussionmentioning
confidence: 89%
“…The surgical procedure of complete obstruction of both ureters has been used in our laboratory and also by other authors 19,21,22 . Campagno et al 21 have recently demonstrated modifications in renal haemodynamic and in some tubular function parameters, as well as in the renal architecture after 5 and 24 hours of bilateral ureteral obstruction. These experimental groups showed interstitial fibrosis, cell desquamation and tubular dilatation, both in proximal tubules and in more distal segments.…”
Section: Discussionmentioning
confidence: 89%
“…In rats, Slc13a2 expression was increased on renal proximal tubule epithelial cells in a model of chemically-induced nephrolithiasis (He et al, 2004b). Nevertheless, renal NaDC1 expression was reduced in a rat model of obstructive nephropathy, which can be caused by nephrolithiasis (Campagno et al, 2018). Finally, the opposing regulation of Slc13a2 in different animal models needs further evaluation.…”
Section: B Solute Carrier 13 Familymentioning
confidence: 98%